2013
DOI: 10.1111/codi.12140
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography has low sensitivity for the diagnosis of early colon cancer

Abstract: CT scanning of colonic cancer showed 75% accuracy in identifying T1 and T2 cancers combined, but gave poor agreement between CT and histopathology for individual T stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
(16 reference statements)
2
15
1
Order By: Relevance
“…This is in line with other reports of between 0 % for T1 to 80 % for T3 tumors [18,19]. When grouping the primary tumor in local limited T0-2 and advanced T3/4, the percentage rose to over 90 % for T3/4 tumors which is quite superior to results from a meta-analysis including 19 studies [17].…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with other reports of between 0 % for T1 to 80 % for T3 tumors [18,19]. When grouping the primary tumor in local limited T0-2 and advanced T3/4, the percentage rose to over 90 % for T3/4 tumors which is quite superior to results from a meta-analysis including 19 studies [17].…”
Section: Discussionsupporting
confidence: 91%
“…The potential for using CT to produce a valid cTN stage has been discussed in several other studies. Some previous studies have shown acceptable agreement between cTN and pTN (5, 9), while others have, as in the present study, shown poor levels of agreement (10,11). Although some studies have presented moderately superior results compared to the current study, they have all struggled to identify high-risk tumors (4,6,911).…”
Section: Discussioncontrasting
confidence: 46%
“…Lao et al . evaluated the accuracy of conventional CT in local staging in colon cancer in 153 tumours. They showed that CT had a sensitivity of 70.2% and a specificity of 79.2%.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis [1] showed that CT is able to detect tumour invasion beyond the bowel wall (T1/T2 vs T3/T4), although the reported studies have a high variability, with wide ranges of sensitivity (55-98%) and specificity (33-100%). Lao et al [30] evaluated the accuracy of conventional CT in local staging in colon cancer in 153 tumours. They showed that CT had a sensitivity of 70.2% and a specificity of 79.2%.…”
Section: Discussionmentioning
confidence: 99%